Biden Administration's Nuclear Posture Review: Analysis and Assessment - Kurosawa, Mitsuru (Journal for peace and nuclear disarmament, 2023)
The Nuclear Posture Review (NPR) by the Biden Administration was published in October 2022. What is its focus and how should we evaluate it? How is it different from previous administrations? Does the NPR reflect Biden's proactive statements before its publication? This article introduces and examines pressing issues of the international security environment and threat perceptions, nuclear deterrence, declaratory policy, arms control, and nuclear capability as reflected in the NPR. Analysis is presented from two aspects, military and diplomacy, as the NPR emphasizes to "put diplomacy first". The military aspects of the NPR, to strengthen and modernize nuclear deterrence as the main role of nuclear weapons, is strongly emphasized. On the other hand, diplomatic aspects of the NPR are narrowly and superficially treated, and it does not include proactive proposals. Future NPRs should include military and diplomatic positions more equally.